Ideological congruence among European political parties - Belchior, Ana Maria (2013)
Do European political parties represent the ideology of their voters well? This research aims to provide an empirical appreciation of the levels to which Members of Parliament (MPs) ideologically represent their electorate within political parties in 12 European countries. The variable used is left–right self-placement and representation is measured through congruence. Three main hypotheses are tested. First, MPs express greater ideological extremism than voters. Second, MPs have biased perceptions on the positioning of their electorate. Third, New Left parties exhibit higher levels of representation than the other parties. This article's findings reveal that only the second hypothesis can be supported without restrictions